Transparency in IPO mechanism: Retail investors’ participation, IPO pricing and returns - Neupane, Suman; Poshakwale, Sunil S. (Journal of Banking & Finance, 2012)
Using data from the transparent Indian IPO setting, the paper examines retail investors’ participation, their influence on IPO pricing and the returns they make on IPO investment. The transparency in the mechanism, which allows investors to observe prior investors’ participation, leads to demand which is concentrated at either one or two points of the offer price range. Analysis of investors’ demand during the offer period shows that the participation of retail investors is significantly influenced by the participation of institutional investors. We examine IPO pricing and find that favourable demand by retail investors is positively associated with a high IPO price even after controlling for demand by institutional investors. Further, we find that due to aggressive bidding by overconfident investors, retail investors are, on average, unlikely to make positive allocation weighted initial returns even in a setting where they do not have to compete with institutional investors. Retail investors, however, can earn significant positive allocation weighted initial returns if they limit their participation in IPOs with above average institutional investors’ demand.